Modelling and experimental research of fault‐tolerant dual‐channel brushless DC motor. Issue 6 (9th April 2018) - Korkosz, Mariusz; Bogusz, Piotr; Prokop, Jan
Abstract : The brushless permanent magnet direct current (DC) machine with dual three‐phase windings is proposed for critical drive systems. It is proposed to call such a solution with a dual stator winding as a dual‐channel brushless permanent magnet DC motor (DCBLDC). The stator windings are supplied by two independent power converters under dual‐channel operation (DCO) mode. After a fault of one channel, a further operation of the machine can be continued in the so‐called single‐channel operation mode (SCO). In this study, a mathematical model of DCBLDC machine which takes into account non‐linearity of a magnetic circuit and all couplings between phases within a given channel as well as between channels is proposed. The results of experimental tests in static and dynamic states for SCO and DCO modes were presented.